2006
DOI: 10.1227/01.neu.0000192683.26584.34
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Perforation Caused by Peritoneal Shunt Catheters:Diagnosis and Treatment

Abstract: BPPC is a neurosurgical emergency. Anal extrusion is present in only a minority of patients; the diagnosis of BPPC is often difficult, delayed, and its incidence is likely underestimated. The majority of patients can be treated with a new peritoneal shunt after cure of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(127 citation statements)
references
References 13 publications
2
118
0
7
Order By: Relevance
“…However, spontaneous bowel perforation is a rare complication from peritoneal catheter and its incidence is between 0.1-0.7% in shunted patients [2,3]. Bowel perforation may manifest immediately after surgery or several years later.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, spontaneous bowel perforation is a rare complication from peritoneal catheter and its incidence is between 0.1-0.7% in shunted patients [2,3]. Bowel perforation may manifest immediately after surgery or several years later.…”
Section: Discussionmentioning
confidence: 99%
“…The ventriculitis, meningitis, intraabdominal abscess and generalized peritonitis that occur due to intestinal perforation are life-threating complications [3]. The most common presentation of bowel perforation is extrusion of catheter thorough anus [2][3][4][5][6]. Wilson et al [4] first reported an intestinal perforation induced by peritoneal catheter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations